Molecular genetic diagnosis and surgical management in a cohort of children with 46,XY disorders/differences of sex development - Wong, Yuenshan Sammi; Luk, Ho Ming; Yau, Ho Chung; Wong, Lap Ming; Poon, Sarah Wing Yiu; Tung, Joanna Yuet Ling; Tam, Yuk Him (Frontiers in Pediatrics, 2025)
ObjectiveA firm diagnosis revealing the etiology of disorders/differences of sex development (DSD) is most helpful in guiding clinical management. The aim of this study is to investigate molecular genetic diagnoses and surgical treatment in a cohort of children with 46,XY DSD.MethodsA retrospective study was conducted on children with 46,XY DSD. They were referred to a tertiary surgical center during the period between 2011 and 2022 and were found to have genetic alterations, which were considered etiologies for their DSD. Data on clinical presentations, sex of rearing, genetic findings, surgical treatment, and comorbidities were collected and reviewed.ResultsA total of 21 patients were included in the study: 11 and 10 were reared as male and female, respectively. Genetic alterations were found as the causes for androgen insensitivity syndrome (n = 4), 5-alpha reductase type II deficiency (n = 5), 17-beta hydroxysteroid dehydrogenase III deficiency (n = 1), 17-alpha hydroxylase deficiency (n = 1), and gonadal dysgenesis (n = 10). Of those with gonadal dysgenesis, the genetic alterations were NR5A1 mutation/deletion (n = 3), DMRT1 deletion (n = 4), WT1 mutation (n = 2), and DAX1 duplication (n = 1). A total of 20/21 patients underwent one or more surgical procedures including hypospadias repair (n = 10), gonadectomy (n = 11), gonadal biopsy (n = 4), hernia repair (n = 4), orchidopexy (n = 1), and feminizing genitoplasty (n = 1). A total of 5/21 had germ cell neoplasms in one or both gonads. A total of 8/10 patients with gonadal dysgenesis had comorbidities involving other systems. Of the whole group, seven patients were found to inherit genetic alterations from their parents.ConclusionsMolecular genetic diagnosis enhances the understanding of etiology, improves diagnostic accuracy, and provides precise guidance in the counseling and surgical management of children with 46,XY DSD.